Theresa May’s Representation of Reality in her Brexit Speeches: Time and Self-projection as Meaningful Values - Dolón Herrero, Rosana (International Journal of English Studies, 2020)
This study analyses Theresa May’s three seminal Brexit speeches. These describe the kind of desirable post-Brexit EU-UK relationship that she envisioned, and together constitute a corpus of 18,532 words. The speeches can be considered as landmarks on a timeline that was initially meant to lead to the delivery of Brexit. It is hypothesized that there may be meaningful differences between the speeches, and that these affect the representation of reality. These in turn would have a bearing on May’s discursive self-representation as either an individualized or a collectivized social actor. To account for such representational values, the study draws on Halliday’s Transitivity System (1994), starting from the clause and its potential to express ideational meanings. With the aim of uncovering more convincing and interesting findings, a statistical analysis is applied.